5HT3 receptors: Target for new antidepressant drugs. (May 2016) - Gupta, Deepali; Prabhakar, Visakh; Radhakrishnan, Mahesh
Graphical abstract: Highlights: 5HT3 receptors are the only ligand gated Cys-loop 'cationotropic' receptors. 5HT3 receptors are abundantly distributed in discrete brain regions. 5HT3 receptor antagonists have antidepressant activity. 5HT3 receptor antagonists can normalize altered neurotransmitter activity, HPA-axis hyperactivity, oxidative stress and neuroplasticity. 5HT3 receptors may be an alternative target in the management of depression. Abstract: 5HT3 receptors (5HT3Rs) have long been identified as a potential target for antidepressants. Several studies have reported that antagonism of 5HT3Rs produces antidepressant-like effects. However, the exact role of 5HT3Rs and the mode of antidepressant action of 5HT3R antagonists still remain a mystery. Here, we provide a comprehensive overview of 5HT3Rs: (a) regional and subcellular distribution of 5HT3Rs in discrete brain regions, (b) preclinical and clinical evidence supporting the antidepressant effect of 5HT3R antagonists, and (c) neurochemical, biological and neurocellular signaling pathways associated with the antidepressant action of 5HT3R antagonists. 5HT3Rs located on the serotonergic and other neurotransmitter interneuronal projections control their release and affect mood and emotional behavior; however, new evidence suggests that apart from modulating the neurotransmitter functions, 5HT3R antagonists have protective effects in the pathogenic events including hypothalamic–pituitary–adrenal-axis hyperactivity, brain oxidative stress and impaired neuronal plasticity, pointing to hereby unknown and novel mechanisms of their antidepressant action. Nonetheless, further investigations are warranted to establish the exact role of 5HT3Rs in depression and antidepressant action of 5HT3R antagonists.